’La Casa Abitata’. Leonardo Savioli tra libertà e ricerca formale - Trivellin, Eleonora (Opus Incertum, 2024)
In 1965 the exhibition La casa abitata was held in the rooms of Palazzo Strozzi in Florence. Thought of as a biennial event, it ultimately had only one edition. Fifteen groups of architects were invited to participate in the exhibition, each assigned a space ranging from approximately 25 to 35 square meters. One of the most notable contributions was that of Leonardo Savioli, who proposed a solution in which architecture, furniture, and functional objects had no hierarchical relationships. The living unit consisted of prefabricated elements, defined by a strongly characterized language that ensured a formal coherence regardless of their arrangement. According to the designer’s intentions, the configuration of the elements could be freely determined by whoever would live in the unit. This project should be interpreted as an open proposal, highlighting how both inhabitants and architects can contribute to the shape of a new model of contemporary living.